Germ Cell Proteins in Melanoma: Prognosis, Diagnosis, Treatment, and Theories on Expression - Ashley M. Rosa; Nitika Dabas; Diana M. Byrnes; Mark S. Eller; James M. Grichnik (Journal of Skin Cancer)
Germ cell protein expression in melanoma has been shown to correlate with malignancy, severity of disease and to serve as an immunologic target for therapy. However, very little is known about the role that germ cell proteins play in cancer development. Unique germ cell pathways include those involved in immortalization, genetic evolution, and energy metabolism. There is an ever increasing recognition that within tumors there is a subpopulation of cells with stem-cell-like characteristics that play a role in driving tumorgenesis. Stem cell and germ cell biology is intertwined. Given the enormous potential and known expression of germ cell proteins in melanoma, it is possible that they represent a largely untapped resource that may play a fundamental role in tumor development and progression. The purpose of this paper is to provide an update on the current value of germ cell protein expression in melanoma diagnosis, prognosis, and therapy, as well as to review critical germ cell pathways and discuss the potential roles these pathways may play in malignant transformation.